Bilingual Education in Asia: Language Use, Academic Impact, and Recommendations for Effective Practices - Daongan, Arcela; Basilio, Gylrihs Gem; Guiniguin, Rose Marie; Pinangi, Adrian; Pelila, John Rey (Journal of Multidisciplinary Research and Development, 2025)
Despite the increasing focus on Bilingual Education (BE) in Asia, driven by globalization and the importance of teaching English, comprehensive analysis comparing teaching methods across countries and their impact on academic performance and language development remains limited. This study reviews BE program implementation, evaluates its effects on students’ academic performance and language skills, and offers suggestions for improving BE practices in Asia. Articles published between 2020 and 2024 were reviewed, focusing on methods utilizing English alongside another language. The study found that BE in Asia uses dual language programs, English as a Medium of Instruction (EMI), and translanguaging techniques to support language and cultural growth. BE in Asia has great potential to improve student’s language skills and cultural understanding. However, its success relies on addressing quality teacher training, support for native languages, and the use of real-world learning experiences. Future research should expand its focus by exploring different databases, studying underused BE methods, examining cultural views on bilingualism, and addressing gaps in teacher training and teaching resources to create more inclusive and effective educational strategies.